Cytochrome c oxidase dysfunction in oxidative stress - Srinivasan, Satish; Avadhani, Narayan G. (Free radical biology & medicine, 2012)
Cytochrome c oxidase (CcO) is the terminal oxidase of the mitochondrial electron transport chain. This bigenomic enzyme in mammals contains 13 subunits of which the 3 catalytic subunits are encoded by the mitochondrial genes. The remaining 10 subunits with suspected roles in the regulation, and/or assembly, are coded by the nuclear genome. The enzyme contains two heme groups (heme a and a3) and two Cu2+ centers (Cu2+ A and Cu2+ B) as catalytic centers and handles more than 90% of molecular O2 respired by the mammalian cells and tissues. CcO is a highly regulated enzyme which is believed to be the pacesetter for mitochondrial oxidative metabolism and ATP synthesis. The structure and function of the enzyme are affected in a wide variety of diseases including cancer, neurodegenerative diseases, myocardial ischemia/reperfusion, bone and skeletal diseases, and diabetes. Despite handling a high O2 load the role of CcO in the production of reactive oxygen species still remains a subject of debate. However, a volume of evidence suggests that CcO dysfunction is invariably associated with increased mitochondrial reactive oxygen species production and cellular toxicity. In this paper we review the literature on mechanisms of multimodal regulation of CcO activity by a wide spectrum of physiological and pathological factors. We also review an array of literature on the direct or indirect roles of CcO in reactive oxygen species production. [Display omitted] ► Mammalian cytochrome oxidase (CcO) is a bigenomic enzyme with 13 subunits. ► The enzyme is regulated by subunit phosphorylation and allosteric effectors. ► CcO function is affected by hypoxia/ischemia, by drugs, and by alcohol. ► CcO function is also compromised in many diseases. ► CcO dysfunction often leads to increased production of reactive oxygen species.